Pengaruh Model Contextual Teaching and Learning (CTL) Terhadap Literasi Kimia Peserta Didik Pada Materi Kesetimbangan Kimia - Baiq Viona Olganita Sugondo; Yayuk Andayani; Ermia Hidayanti (FKIP University of Mataram, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on students’ chemistry literacy regarding chemical equilibrium. The study employed a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design. The research sample consisted of 11th-grade students at SMAN 1 Pujut selected through cluster random sampling, with class XI F1 serving as the control group and class XI F2 as the experimental group receiving CTL-based instruction. The instrument used was a two-tier multiple-choice chemistry literacy test covering scientific and chemical content knowledge as well as higher-order learning skills. The content validity of the instrument was tested using Aiken’s V index, yielding a value of 0.88, indicating that the instrument falls within the valid category. The reliability of the instrument was tested using Cronbach’s Alpha coefficient, yielding a value of 0.74, indicating that the instrument has a high level of reliability and is therefore suitable for use in this study. The ANCOVA test results showed that the CTL model had a significant effect on students' chemical literacy (p=0.000<0.05) with a contribution of 29.7%. In the content aspect, the experimental class obtained 81%, higher than the control class at 72.5%. In the aspect of higher-order learning abilities, the experimental class reached 46.5%, while the control class only 15%. Overall, the chemical literacy of the experimental class was in the moderate category (64%), while the control class was in the low category (43.75%). This indicates that the CTL model is effective in improving chemical literacy because contextual learning helps students understand the concept of chemical equilibrium in a more meaningful and applicable way.